Eye-movement reveals word order effects on comparative sentences in older adults using a verb-final language - Hwang, Jihyun; Lee, Seunghun J.; Sung, Jee Eun (Frontiers in Psychology, 2024)
Objectives: This study aimed to examine age-related differences in the comprehension of comparative sentences in Korean by employing both offline and online measures, and to investigate how variations in word order influence this comprehension.Methods: A total of 26 young adults and 26 older adults conducted a sentence-picture-matching task under two different word order conditions: comparative-first and nominative-first. Eye movements were recorded during the task.Results: Older adults demonstrated lower accuracy and longer response times compared to young individuals. Additionally, distinctive patterns were observed across different age groups, with the older group showing greater target advantage scores on the sentential-final phrase in the comparative-first sentences.The study revealed distinctive fixation patterns between the two age groups based on word order manipulations, indicating different processing strategies are engaged between young and older groups. Our research also highlights that even comparative sentences can reveal age-related changes in sentence comprehension.